The Gospel and Economic Disorder: Ephesus and the Cult of Artemis - C. Eric Turner (Religions)
This paper will explore the background of how the first-century cult of Artemis was central to the economy of Ephesus, and subsequently, how Paul’s preaching of the gospel caused an economic disruption during his visit to the city, as narrated in Acts 19:21–41. The goal will be to show how theology and economics are interrelated and, as a result, establish the proper domain for advancing human flourishing in our modern society. The lens through which this paper is seeking to understand economics is through what is known as substantivism over and against formalism, or an empirical-based approach against a deductive–abstract methodology. The substantivist position is undertaken here primarily to explain how economic life is embedded in non-economic structures (here, the cult of Artemis).